Neurotensin Phosphorylates GSK-3α/β through the Activation of PKC in Human Colon Cancer Cells - Wang, Qingding (Neoplasia Press Inc., 2006)
Neurotensin (NT), a gastrointestinal hormone, binds its receptor [neurotensin receptor (NTR)] to regulate the growth of normal and neoplastic intestinal cells; molecular mechanisms remain largely undefined. Glycogen synthase kinase-3 (GSK-3) regulates diverse cellular processes, including cell growth and apoptosis. Here, we show that NT induces the phosphorylation of GSK-3α/β in the human colon cancer cell line HT29, HCT116, or SW480, which possesses highaffinity NTR. The effect of NT was blocked by inhibitors of protein kinase C (PKC), but not by inhibitors of mitogen-activated protein kinase/extracellular signalregulated kinase (MEK1) or phosphatidylinositol-3 kinase, suggesting a predominant role for PKC in GSK-3β phosphorylation by NT. Pretreatment with Gö6976 (which inhibits PKCα and PKCβ1) or downregulation of endogenous PKCα or PKCβ1 blocked NT-mediated GSK-3β (but not GSK-3α) phosphorylation. Moreover, a selective PKCβ inhibitor, LY379196, reduced NT-mediated GSK-3β (but not GSK-3α) phosphorylation, suggesting a role for PKCβ1 in the NT-mediated phosphorylation of GSK-3β and an undefined kinase in the NT-mediated phosphorylation of GSK-3α. Treatment with NT or the GSK-3 inhibitor SB216763 increased the expression of cyclin D1, a downstream effector protein of GSK-3 and a critical protein for the proliferation of various cells. Our results indicate that NT uses PKC-dependent pathways to modulate GSK-3, which may play a role in the NT regulation of intestinal cell growth.